Implementation of Inward Manifest Notification Management Based on Regulation of The Minister of Finance - Lia Alvianita; Yosi Pahala; Gena Bijaksana (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
This research aimed to evaluate the implementation of inward manifest notification procedures on PT Bollore Logistics Indonesia in the air import business unit.. The research method used are interview, observation, and documentation. The number of research samples was four people taken through purposives way. Data analysis using descriptive qualitatives. Based on the results of the triangulation and evaluation carried out on the implementation of inward manifest submission on PT Bollore Logistics Indonesia, it is known that the submission process of the implemented inward manifest has several process characteristics and the achievement of targets from the submission of inward manifest is still fluctuating because it is influenced by existing obstacles. The conclusion of the study is that at the stage of the implementation of the inward manifest submission which applicable in PT Bollore Logistics Indonesia, need to be added several stages that can help to minimize the occurrence of errors in the notification process and determine how to overcome the obstacles that have occurred to achieve the company's targets.